Deep brain stimulation: a mysterious success or a clue to help localize the causes of Parkinsonism? - Arbuthnott, Gordon (Henry Stewart Talks, 2014)
Deep Brain Stimulation has been a huge success for the relief of motor symptoms in Parkinson’s disease but no-one is sure how it works, DBS was designed to resolve problems that fitted an out of date version of how the basal ganglia are changed by the disease, This talk suggests an alternative, more modern, explanation of its effects.